Elaboración y aplicación de antígeno parasitario (haemonchus) en Ovinos - Pilataxi Simbaña, Jhonny Damian (2021)
In this research project, the parasitic antigen for Haemonchus was evaluated in sheep, by means of immunological tests to induce an immune response and improve production in the different farms, starting with their identification records, later the sheep were dewormed with levamisol, months later. Parasites were collected in sacrificed animals to be taken to the laboratory to elaborate the antigen, once the protein was obtained it was sent to Agrocalidad for its respective quantification by the Kjeldahl method, the results were obtained, stool and blood samples were taken for their coproparasitic and immunochemical examinations For their respective analyzes, the next day the vaccine was inoculated in the caudal fold of the 25 sheep, we waited for an immune response of 19 days post inoculation to perform the second immunochemical examination, once the samples were sent to the laboratory, the animals were sent a polluted pasture of hae monchus and wait 19 days for their biological cycle to be completed and perform the second coproparasitic test and check for the presence of parasites. Obtaining in the first coproparasitic results of 80% positive and 20% negative. In the second post-inoculation coproparasitic, 16% positive and 84% negative were obtained. The immunochemical results at the beginning of the investigation showed that 70% of the sheep are below the normal reference values and at the end 30% present low values of the normal values. In immunoglobulin E results, at the beginning 20% exceed the normal reference values and at the end they present 30% indices that exceed the normal reference values. These results produced a reduction in economic costs in deaths, weight loss, and very high veterinary drug costs, being beneficiaries for sheep producers.